1996
DOI: 10.1111/j.2042-7158.1996.tb05911.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Powder Plug Formation Using a Simulated Capsule Filling Machine

Abstract: Using an apparatus which simulates the action of a Macofar 13‐2 dosating‐type capsule‐filling machine, the variation in plug weight and density with changing machine parameters has been studied. The piston ejection speed has no effect on plug properties. However increase in compression speed leads to a less consolidated powder plug and hence reduced plug weight. Application of higher pressures reduces plug weight changes, but would be expected to affect release characteristics. Comparison of axial and radial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Only the simulator designed and constructed by Britten and Barnett comes closest to those that have been developed for simulating tablet compaction in terms of meeting the objectives of simulation. In a study of plug formation using this simulator, Britten et al (4) made a number of observations which often confirmed data reported by others using instrumented capsule filling machines.…”
Section: Introductionsupporting
confidence: 52%
“…Only the simulator designed and constructed by Britten and Barnett comes closest to those that have been developed for simulating tablet compaction in terms of meeting the objectives of simulation. In a study of plug formation using this simulator, Britten et al (4) made a number of observations which often confirmed data reported by others using instrumented capsule filling machines.…”
Section: Introductionsupporting
confidence: 52%
“…As discussed previously, materials that exhibit substantial elastic behavior may recover differently in the 2 machines, thereby leading to greater ejection forces in the dosator machine. While it is conceivable that such a theory could apply to the lactose-based model lubricity formulations, lactose exhibits substantially less elastic recovery than Starch 1500 5 and a substantially higher lubricant requirement than either Starch 1500 3,5 or microcrystalline cellulose. 3 Clearly, any possible greater powder shearing in the dosing disc machine, as suggested by Ullah and colleagues, 19 would tend to increase the lubricant efficiency in that machine, thereby leading to easier ejection.…”
Section: Lubricity Formulationsmentioning
confidence: 99%
“…Britten and colleagues 5 discussed this phenomenon in the context of Starch 1500. On the basis of measurements made on an instrumented Macofar dosator machine simulator, Britten and colleagues 5 found for Starch 1500 plugs, which exhibit considerable elastic recovery, that residual radial pressure was lower than that for lactose and that the ejection pressures were undetectable. Microcrystalline cellulose, used as the model flow material, also exhibits substantial postcompression elastic recovery, 18 which at least in part accounts for this material's ability to be run without lubricant.…”
Section: Flow Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, lower machine speed is advised when AL is used as filler for high drug load formulation (Figure 4). Britten et al 51 reported that increase in precompression speed caused a fall in plug weight of pregelatinized starch and lactose. They found that at higher speeds, powder is pushed ahead of the nozzle rather than entering it, and therefore, there is less consolidation, which leads to a lower plug breaking force.…”
Section: Effect On Plug Strengthmentioning
confidence: 98%